Effects of the Peripheral Substituents, Central Metal, and Solvent on the Photochemical and Photophysical Properties of 5, 15‐Diazaporphyrins. Issue 6 (4th March 2019) - Omomo, Satoshi; Fukuda, Ryosuke; Miura, Tomoaki; Murakami, Tatsuya; Ikoma, Tadaaki; Matano, Yoshihiro
Abstract: Metal complexes of 3, 7, 13, 17‐tetrakis(di(4‐carboxyphenyl)amino)‐5, 15‐diazaporphyrin (MDAP‐COOH; M=Pd, Cu) and their ethyl ester precursors (MDAP‐COOEt; M=Pd, Cu) have been synthesized for use as near‐infrared (NIR)‐light‐responsive photosensitizers. Under irradiation with visible or NIR light, PdDAP‐COOEt in toluene generated singlet oxygen ( 1 O2 ) with an excellent quantum yield ( Φ Δ =0.99), whereas CuDAP‐COOEt exhibited a lower efficiency ( Φ Δ =0.21). The water‐soluble Pd II complex PdDAP‐COOH also behaved as a photosensitizer ( Φ Δ =0.20) in a micellar solution. The photophysical properties of these dyes were measured by transient absorption techniques. It was found that the efficiency of the energy transfer from the triplet state of MDAP‐COOR (R=Et, H) to the ground state of dioxygen was highly dependent on the peripheral substituents, the central metal, and the solvent. Furthermore, the phototoxicity of PdDAP‐COOH toward HeLa cells under irradiation of NIR light (720 nm) was evaluated. As expected, PdDAP‐COOH exhibited good photodynamic activity, and control experiments confirmed that 1 O2 was generated as the active oxygen species. Abstract : Efficient sensitizers : A series of metallated water‐soluble 5, 15‐diazaporphyrins act as singlet oxygen photosensitizers under irradiation with visible or near‐infrared (NIR) light. The peripheral substituents, central metal, and solvent all influence the photochemical and photophysical properties of the diazaporphyrin ring. The water‐soluble palladium(II) complex exhibited remarkable phototoxicity toward HeLa cells under irradiation with NIR light.